2008
DOI: 10.1016/j.diabres.2007.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of apathy on glycemic control in diabetes: A cross-sectional study

Abstract: Apathy is highly prevalent in patients with diabetes without depression. Apathy may have a negative impact on self-care behaviors and diabetes control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
(30 reference statements)
1
39
0
Order By: Relevance
“…In a large community based study, there was an association, albeit not statistically significant, between diabetes and apathy scores in the sub-sample with no history of stroke (10). There have been few studies in diabetes but a recent study from a clinic population reported that 50 out of 81 older diabetic patients had apathy, which was associated with reduced adherence to self-management behaviours, obesity and a non-significantly increased HbA 1c level (12). The authors subsequently reported that methylphenidate treatment improved glycemic control in 8 apathetic diabetic patients with Alzheimer's disease (13).…”
Section: Accepted Manuscriptmentioning
confidence: 91%
See 1 more Smart Citation
“…In a large community based study, there was an association, albeit not statistically significant, between diabetes and apathy scores in the sub-sample with no history of stroke (10). There have been few studies in diabetes but a recent study from a clinic population reported that 50 out of 81 older diabetic patients had apathy, which was associated with reduced adherence to self-management behaviours, obesity and a non-significantly increased HbA 1c level (12). The authors subsequently reported that methylphenidate treatment improved glycemic control in 8 apathetic diabetic patients with Alzheimer's disease (13).…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…Baseline PHQ-9 scores were also significantly different among the four conditions (Kruskall-Wallis H test, chi-square 8.29, df 3, P=0.04 ) with lower median depression scores at baseline (that approached statistical significance) in recovered compared with persistent apathy (2[2][3][4] vs 13[7][8][9][10][11][12][13][14][15][16], P=0.053). There were no differences in MMSE scores (Kruskall-Wallis H test, chi-square 6.63, df 3, P=0.09).…”
mentioning
confidence: 98%
“…Arigo et al [6] showed that social support mediated the relationship between depressive symptoms and glycemic control. In addition, apathy and perceived control are other psychological constructs implicated in glycemic control regardless of the severity of depression [7,13]. Diabetes-specific emotional distress has also been extensively studied and is reported as a better predictor of diabetes self-care than depression [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…One of the determining factors for lack of control of chronic diseases, and especially for diabetes mellitus, comprises the prejudices and stereotypes that deriving form lack of information, which leads to negation of the disease and abandonment of treatment, or resorting to "miraculous or cure-all" treatments. On the other hand, it has been demonstrated that apathy is one of the principal difficulties for the population in its adoption of healthy lifestyles for chronic disease prevention and control (Padala et al, 2008). Thus, our proposal establishes the elimination of the stigma of the disease and proposes a model of community intervention for integral human development in which maintenance of health constitutes the key factor.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Among the most relevant aspects of the model, we find that community groups are not labeled with "groups of diabetics" stigma. In this regard, it has been proposed that unfundamented social representations of diabetes leads to prejudices on and negative stereotypes of the disease (Torres-López et al, 2005) that affect self-esteem, causing apathy, rejection, and abandonment of the "groups of diabetics" (Padala et al, 2008). On the other hand, the anthropological aspects associated with the disease should be considered in community interventions, because cultural aspects determine negative lifestyles (sedentary life style and inadequate nutrition), which raises the risk of diabetes mellitus (Martorell, 2005).…”
Section: Model Viabilitymentioning
confidence: 99%